Felsic Xenocryst in the Bedded Porcellanite (Mesoproterozoic) of the Central India: An Evidence Suggesting the Rhyolitic Source of Silica - Krishna Mondal; B. P. Singh (Global Journal of Earth Science and Engineering, 2017)
The Mesoproterozoic porcellanite of the Vindhyan Super group is the oldest porcellanite deposit of India. Its origin is poorly understood in the absence of silica secreting organisms during Proterozoic times and earlier. Here, we interpret the origin and possible source of silica based on sedimentary structures and xenocryst occurring in these porcellanites. Lithofacies and related sedimentary structures suggest that the studied porcellanite precipitated in a shallow marine condition in the intracratonic Vindhyan basin. Four different facies types are recognised within the porcellanite; these are yellow, black, white and green chert / porcellanite. Based on physical characteristics, it is suggested that the black and green porcellanites are chert and yellow and white porcellanites are either rhyolite or porcellanie.ellow and white porcellanite are either rhyolite or porcellanite. The presence of felsic xenocryst, including sanidine, encased within the microcrystalline and cryptocrystalline quartz suggests that the source of silica was a rhyolite. The quartz of the felsic volcanic rock (rhyolite) was dissolved in the seawater during alkaline pH created by the presence of phytoplanktons and the dissolved silica got precipitated in the form of bedded chert and porcellanite during lowering of the pH coupled with the evaporation of the seawater. The intermittent supply of the clay as impurities in the silica originated true porcellanite in the present case.